Quality Of Nastar Corn Flour - Wahyuni, Sukma; Holinesti, Rahmi; Gusnita, Wiwik; Anggraini, Ezi (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
Nastar is a type of cookie made from a dough of flour, butter and eggs filled with pineapple jam with a brittle, crunchy, slightly gritty texture and sweet taste. The background of this research is because there is no utilization of corn flour raw material in nastar processing. Utilization of corn flour aims to reduce dependence on wheat flour, as well as add nutritional value to nastar. Based on this, this study aims to determine the effect of corn flour substitution of 0%, 15%, 30%, and 45% on the quality of shape, color, aroma, texture and taste of the resulting nastar. This type of research is a pure experiment using a completely randomized design (CRD) with three repetitions. The type of research data is primary data sourced from 3 panelists. Data were analyzed using analysis of variance (ANAVA). If there is a significant effect then proceed with Duncan's test. The results of the study showed that the substitution of nastar corn flour had an effect on the quality of the fragrant aroma of corn and the taste of nastar corn because fcount > ftable. While the shape (neat and uniform), texture, color, and sweet nastar taste did not show a significant effect. The best overall score is uniform shape 3.78 (X2), neat shape 3.78 (X1), color 3.78 (X2), sweet corn nastar aroma 2.89 (X3), texture 3.89 (X2) taste sweet nastar 3.67 (X3). The best result in this study was treatment X1 with 15% corn flour substitution.